2022
DOI: 10.3390/s22082865
|View full text |Cite
|
Sign up to set email alerts
|

Method for Film Thickness Mapping with an Astigmatic Optical Profilometer

Abstract: An astigmatic optical profilometer is a precision instrument with advantages such as high resolution, high bandwidth, a compact size, and low cost. However, current astigmatic optical profilometers measure only surface morphology, and their potential for capturing subsurface information remains underutilized. In this study, we developed a method for measuring the thickness of transparent thin films with an astigmatic optical profilometer. Experimental results demonstrate that the thickness of transparent films… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…Profilometer on the other hand is an easy to use and compact optical profiler. The main advantages of the profilometer are its fast scanning speed, which results in a reaction time of the distance sensor that is less than 0.1 ms, high bandwidth, a compact size, and low cost [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Profilometer on the other hand is an easy to use and compact optical profiler. The main advantages of the profilometer are its fast scanning speed, which results in a reaction time of the distance sensor that is less than 0.1 ms, high bandwidth, a compact size, and low cost [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the astigmatic profilometer is able to provide a high spatial resolution image, which has been utilized for various applications, such as bio-molecular sensing and cell imaging [18][19][20]. Previous studies have demonstrated that the astigmatic profilometer can measure not only the surface morphology but also the film thickness [21]. Moreover, the z-axis modulation mode of the astigmatic profilometer enables measurement of the S curve at each image pixel [22,23].…”
Section: Introductionmentioning
confidence: 99%